Pengaruh Likuiditas dan Return on Equity (ROE) Terhadap Return Saham - Efendi Trias Yusnita; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The capital market provides facilities for channeling funds from those who have funds to those who need funds. Capital market performance is affected by many factors, and 2 of them are company liquidity and company profitability. Researchers will conduct research on companies listed on the Indonesia Stock Exchange in 2020-2021. This type of research is associative research. Independent variables are Stock liquidity (X1) and Return On Equity (X2), and depended variable is Stock Return (Y). The data used in this research is secondary data obtained from www.idx.co.id, www.yahoo.finance.co.id. The time of this research was conducted from July 2022 to January 2023. The population in this study were all companies registered on the Jakarta Islamic index for the period 2020 to 2021 with a total sample is 15 companies. Result of the study showed that stock liquidity (X1) and return on equity (X2) either simultaneously and partially have no significant effect on the Rate of Return (Y). This result showed that stock market participant did not using information from fundamental information of the company. They were prefer using technical method than fundamental method.Keywords: Return on equity value, liquidity value, H0 accepted, normality test, heteroscedasticity test